Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose $X$ has the $\mathrm{Poisson}(5)$ distribution considered earlier.

Then $P(X \in A) = \sum_{j\in A} \frac{e^{-5}5^j}{j!}$, which implies that $L(X) = \sum^\infty_{j=0} \left(\frac{e^{-5}5^j}{j!}\right)\delta_j$, a convex combination of point masses. The following propostion shows that we have $E(f(X)) = \sum_{j=0}^\infty\frac{f(j)e^{-5}5^j}{j!}$ for any function $f : \mathbb{R} \rightarrow \mathbb{R}$.

Prop. Suppose $\mu = \sum_i \beta \mu_I$ where $\{\mu_i\}$ are probability distributions, and $\{\beta_i\}$ are non-negative constants (summing to 1, if we want $\mu$ to also be a probability distribution). Then for Borel-measurable functions $f : \mathbb{R} \rightarrow \mathbb{R}$,

$$\int fd\mu = \sum_i \beta_i \int f \, d\mu_i,$$

provided either side is well-defined.

Using this proposition:

Let $X \sim \mathrm{Poisson}(5)$.

(a) compute *E*$(X)$ and *Var*$(X)$.

(b) compute *E*$(3^X)$.

I know that the answers from a previous question are: $E[X]=\lambda$, $E[X^2]=\lambda+\lambda^2$ (from the previous two, you could compute the variance) and $E[e^{3X}]= e^{2 \lambda}$.

However, I'm not sure as to how to get to this other than I'm supposed to use a Taylor series.

share|cite|improve this question
I am not understanding your problem. You have the formulas you need: just replace $\lambda$ with 5 and simplify. – echoone Dec 4 '12 at 2:34
What does "earlier" refer to? – joriki Dec 4 '12 at 2:38
possible duplicate of Poisson distribution and probability distributions – Micah Dec 4 '12 at 5:05
up vote 2 down vote accepted

The Poisson distribution is the limit of the binomial distribution as the number of trials approaches infinity. The binomial distribution function is given by $$p(y) = {n \choose y} p^y (1-p)^{n-y}.$$ Let $\lambda = np$, and take the limit as $n \to \infty$. $$\lim_{n \to \infty} {n \choose y} p^y (1-p)^{n-y} = \lim_{n \to \infty} \frac{n(n-1) \cdots (n-y+1)}{y!} \left(\frac{\lambda}{n}\right)^y \left(1 - \frac{\lambda}{n}\right)^{n-y}$$ $$= \lim_{n \to \infty} \frac{\lambda^y}{y!} \left(1 - \frac{\lambda}{n}\right)^n \frac{n(n-1) \cdots (n-y+1)}{n^y} \left(1 - \frac{\lambda}{n}\right)^{-y}$$ $$= \frac{\lambda^y}{y!} \lim_{n \to \infty} \left(1 - \frac{\lambda}{n}\right)^n \left(1 - \frac{\lambda}{n}\right)^{n-y} \left(1 - \frac{1}{n}\right) \left(1 - \frac{2}{n}\right) \cdots \left(1 - \frac{y-1}{n}\right).$$ Then, we can use the identity $$\lim_{n \to \infty} \left(1 - \frac{\lambda}{n}\right)^n = e^{-\lambda},$$ and since the rest of the terms in the limit converge to $1$, we have $$p(y) = \frac{\lambda^y}{y!}e^{-\lambda}.$$

Now, we can find the expected value and variance using $$E(Y) = \sum_{y=0}^\infty y\frac{\lambda^y e^{-\lambda}}{y!} = \sum_{y=1}^\infty \frac{\lambda^y e^{-\lambda}}{(y-1)!}.$$ Factor out $\lambda$, and substitute $z = y - 1$ to get $$E(Y) = \lambda \sum_{z=0}^\infty \frac{\lambda^z e^{-\lambda}}{z!}.$$ Since the sum is over an entire probability distribution, it converges to $1$, and thus the expected value is $\lambda$.

The variance is given by $$V(Y) = E(Y^2) - E(Y)^2.$$ We already know $E(Y)^2 = \lambda^2$, so what remains is $E(Y^2)$. $$E(Y^2) = \sum_{y=0}^\infty y^2 \frac{\lambda^y e^{-\lambda}}{y!}$$ which simplifies in a similar manner to $$E(Y^2) = \lambda^2 + \lambda.$$

Thus, $V(Y) = \lambda$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.